Formulação do método dos elementos de contorno para a flexão de placas duplas conectadas por camada elástica de Pasternak - Pereira, Arthur Coutinho de Araújo (2023)
In this work, a formulation of the Boundary Element Method (BEM) for static analysis of two parallel plates connected by an elastic Pasternak layer is develop. The fundamental solution is obtained using the Hӧrmander operator and the integral equations are derived using Betti's reciprocity theorem. Some cases of plates with different properties, boundary conditions and loading are studied and their results obtained via BEM are validated through analytical responses. The BEM results for the double plate system recovered the analytical results satisfactorily and also showed that the stiffness of the plates and the elastic foundation constants play a relevant role in the transmissibility of effects in the plate system.